Two new species of Xenysmoderodes from China (Coleoptera: Curculionidae: Ceutorhynchinae) - Yang, Ni; Zhang, Runzhi; Ren, Li (Zootaxa, 2013)
Xenysmoderodes Yoshitake, 2007, belonging to the tribe Mecysmoderini, was described as a monotypic genus from Japan, including the species X. sasajii Yoshitake. Two new species, X. concavus sp. nov. and X. flos sp. nov., are described here fromChina, providing a new country record for this genus. We revise the description of the genus based on three species and present an updated key to the species.